Rugby academy - Palmer, Tom (Edinburgh: Conkers, 2019)
Borderlands First XV have their sights set on becoming the best school rugby team in the world. But while the boys focus on their matches, many of their parents are serving overseas in the armed forces, and everyone is worried as conflict grows in the Central Asian Republic. New pupil Woody is a footballer by nature and must decide if he's prepared to give rugby his all. Rory feels like he's losing his focus, distracted by thoughts of his parents in danger. And Owen finds himself a t the centre when conflict breaks out within the team. With so many hurdles to face along the way, how far will they get in the rigorous schools' tournament?
Keywords: High interest-low vocabulary books